2015
DOI: 10.1080/19336950.2015.1027849
|View full text |Cite
|
Sign up to set email alerts
|

Study of permeation and blocker binding in TMEM16A calcium-activated chloride channels

Abstract: We studied the effects of mutations of positively charged amino acid residues in the pore of X. tropicalis TMEM16A calcium-activated chloride channels: K613E, K628E, K630E; R646E and R761E. The activation and deactivation kinetics were not affected, and only K613E showed a lower current density. K628E and R761E affect anion selectivity without affecting Na C permeation, whereas K613E, R646E and the double mutant K613E C R646E affect anion selectivity and permeability to Na C . Furthermore, altered blockade by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…We (this study) and others (Bradley et al ., ; Reyes et al ., ) showed that extracellular A9C only effectively blocked TMEM16A currents at positive V m . This is consistent with a model in which the inhibitory A9C binding site is accessible from the extracellular side and is situated within a region that spans the electric field of the membrane.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…We (this study) and others (Bradley et al ., ; Reyes et al ., ) showed that extracellular A9C only effectively blocked TMEM16A currents at positive V m . This is consistent with a model in which the inhibitory A9C binding site is accessible from the extracellular side and is situated within a region that spans the electric field of the membrane.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Reyes et al . () reported that A9C inhibited Xenopus laevis TMEM16A channels in a V m ‐dependent manner with a K i of ~90 μM at +80 mV. Bradley et al .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…; Reyes et al . ) and residues near the top of the cleft have been identified as forming the vestibule and contributing to ionic selectivity (residues G628–M532 and I636–Q637; Yu et al . ) shown in red and residues R515, K603, R621 and R788 (Peters et al .…”
Section: Discussionmentioning
confidence: 99%